2017
DOI: 10.1007/s00429-017-1365-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ventral tegmental area dopamine neurons produces wakefulness through dopamine D2-like receptors in mice

Abstract: A growing body of evidence suggests that dopamine plays a role in sleep-wake regulation, but the dopamine-producing brain areas that control sleep-wake states are unclear. In this study, we chemogenetically activated dopamine neurons in the ventral midbrain of mice to examine the role of these neurons in sleep-wake regulation. We found that activation of dopamine neurons in the ventral tegmental area (VTA), but not in the substantia nigra, strongly induced wakefulness, although both cell populations expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 33 publications
5
80
0
Order By: Relevance
“…This brain region may be an important part of the intrinsic system that controls sleep and wakefulness3536. The present genetic findings support data collected in animals242526272857 and observations from brain imaging30394042 and epidemiological38 studies in humans, suggesting prominent roles for DAT and D 2 receptors in sleep-wake regulation. They highlight the importance of the striatum in regulating changes in vigilant attention, subjective sleepiness, and neurophysiological EEG oscillations during prolonged wakefulness.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This brain region may be an important part of the intrinsic system that controls sleep and wakefulness3536. The present genetic findings support data collected in animals242526272857 and observations from brain imaging30394042 and epidemiological38 studies in humans, suggesting prominent roles for DAT and D 2 receptors in sleep-wake regulation. They highlight the importance of the striatum in regulating changes in vigilant attention, subjective sleepiness, and neurophysiological EEG oscillations during prolonged wakefulness.…”
Section: Discussionsupporting
confidence: 88%
“…Recent chemogenetic and optogenetic studies in flies and mice confirmed this crucial role of dopamine in regulating sleep-wake behaviors222324. Nevertheless, the contribution of the dopaminergic system to sleep-wake regulation in humans is still only poorly described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep-Wake Patterns and Arousal. Activation of VTA DAergic neurons by hM3Dq was shown to increase wakefulness periods while reducing sleep-associated behaviors, such as nest building, in both stages of the light/dark cycle in a D 2 R-dependent manner (Oishi et al, 2017a;Sun et al, 2017). Further investigations revealed that NAc D 1 R-and NAc core adenosine A2a receptorexpressing neurons also regulated these sleep-wake patterns (Oishi et al, 2017b;Luo et al, 2018).…”
Section: Modulating Dopamine Signaling and Behavior With Chemogeneticsmentioning
confidence: 96%
“…A large‐scale candidate gene sequencing project reported a single nucleotide polymorphism (SNP) within intron 1 of dopamine receptor D2 ( DRD2 ) to be significantly associated with self‐reported sleep duration and suggestively associated with sleep latency determined by EEG (Cade et al., ). Consistently, work in mice revealed that activation of dopamine neurons in the ventral tegmental area promotes wakefulness via D2‐like receptors (Oishi et al., ). Furthermore, the dopamine system is known to play critical roles in regulating the quantity and quality of sleep in multiple organisms (Cirelli, ).…”
Section: Sleep Quantity and Qualitymentioning
confidence: 72%